Intelligent piracy site detection technique with high accuracy - Kim, Eui Jin; Kwak, Jin (KSII Transactions on Internet and Information Systems, 2021)
Recently, with the diversification of media services and the development of smart devices, users have more opportunities to use digital content, such as movies, dramas, and music; consequently, the size of the copyright market expands simultaneously. However, there are piracy sites that generate revenue by illegal use of copyrighted works. This has led to losses for copyright holders, and the scale of copyrighted works infringed due to the ever-increasing number of piracy sites has increased. To prevent this, government agencies respond to copyright infringement by monitoring piracy sites using online monitoring and countermeasure strategies for infringement. However, the detection and blocking process consumes a significant amount of time when compared to the rate of generating new piracy sites. Hence, online monitoring is less effective. Additionally, given that piracy sites are sophisticated and refined in the same way as legitimate sites, it is necessary to accurately distinguish and block a site that is involved in copyright infringement. Therefore, in this study, we analyze features of piracy sites and based on this analysis, we propose an intelligent detection technique for piracy sites that automatically classifies and detects whether a site is involved in infringement.
Keywords: Blocking process; Copyright holders; Copyright infringement; Countermeasure strategies; Digital contents; Government agencies; Intelligent detection; Online monitoring; Copyright Infringement; Copyright Protection; Digital Content; Government Monitoring; Piracy Site